Angiotensin converting enzyme inhibitors, angiotensin receptor blockers, mineralocorticoid receptor antagonists and SARS-CoV-2 infection - Valera, Pratiksha; Letuka, Pheletso; Mathenjwa, Nontobeko; Ntusi, Ntobeko (SA Heart Journal, 2020)
Angiotensin converting enzyme inhibitors (ACE-Is), angiotensin receptor blockers (ARBs) and mineralocorticoid receptor antagonists (MRAs) reduce morbidity, mortality and hospitalisations from hypertension, chronic kidney disease and heart failure. Patients and clinicians will be aware of the recently publicised interaction between the renin-angiotensin-aldosterone system (RAAS) and SARS-CoV-2, the orthocoronavirus responsible for coronavirus disease 2019 (COVID-19). Consequently, concern has abounded in regard to whether prescribed blockers of the RAAS like ACE-Is, ARBs and MRAs may, in fact, increase or decrease susceptibility to SARS-CoV-2 infection. Limited scientific evidence has been contradictory. Scientists have postulated both potentially harmful and potentially beneficial effects of these drugs on the natural history of COVID-19. Membrane-bound angiotensin-converting enzyme 2 (ACE2) participates in the entry of SARSCoV-2 into human cells, and animal studies show that ACE-Is and ARBs upregulate ACE2 expression, which would theoretically increase risk for or severity of COVID-19. Conversely, RAAS blockers could benefit patients with COVID-19 through various mechanisms: ACE2 converts angiotensin II to angiotensin, which has potentially beneficial vasodilatory and anti-inflammatory properties. Observational studies have failed to provide compelling data on whether COVID-19 patients on RAAS blockers fare better or worse than otherwise similar patients, though there is emerging evidence that RAAS inhibitors may be protective in COVID-19 and are associated with lower cardiovascular and all-cause mortality. Most professional societies, including the World Health Organization and the South African Heart Association and the South African National Department of Health have recommended that patients on RAAS blockers with COVID-19 should continue taking them. In this article, we review the existing evidence for the interplay between RAAS blockers and SARS-CoV-2 infection.